(3LhGeY GdEScfOQGfjjf dcJGH LGdjfhS aj aQb GdWHs ((3YKeGf Hf Ydi Hf eMeO GdSeQbfOj s)
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI GdebGdI GdChdj ef cJGH LGdjfhS aj Gdbhj GdWHjYjI fbd CHj RjO Mfjf Hf GSMGb Gdbhj KdGKI GLfGS eJTGHgI hefgG faSjI hefgG MjhGfjI s
(3BNQgG (B:s
(3CUMGH GdYdI GdeYQhaI HGdJTfL jehJhf hCHOGfge HYO MGQ , hCUMGH GdZT jehJhf HYO Cf jHQO efge LejY GdHOf s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs